2016
DOI: 10.1136/annrheumdis-2016-eular.1705
|View full text |Cite
|
Sign up to set email alerts
|

AB0765 Identification of Neuropathic Pain Component in Patients of Various Age with Knee Osteoarthritis

Abstract: BackgroundOsteoarthritis-induced pain is a result of nociceptor stimulation, associated with local tissue damage and inflammation. Resent data suggest the presence of neuropathic pain symptoms in patients with osteoarthritis.ObjectivesThe aim of this study was to estimate the structure of pain syndrome, reveal the presence of neuropathic pain (NP) component, symptoms and signs of NP in patients suffering from knee osteoarthritis.MethodsWe've examined 44 patients with knee osteoarthritis of the II-III stages by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In agreement with our results, several studies reported the frequency of neuropathic pain in patients with KOA which was ranged from 17.6 to 51.9% (based on the DN4 questionnaire and/or LANSS scale) [26][27][28][29][30][31][32][33][34]. Other studies reported neuropathic pain in OA patients (based on the painDETECT questionnaire) in frequencies ranged from 20.7 to 66.7% [31,[35][36][37].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our results, several studies reported the frequency of neuropathic pain in patients with KOA which was ranged from 17.6 to 51.9% (based on the DN4 questionnaire and/or LANSS scale) [26][27][28][29][30][31][32][33][34]. Other studies reported neuropathic pain in OA patients (based on the painDETECT questionnaire) in frequencies ranged from 20.7 to 66.7% [31,[35][36][37].…”
Section: Discussionsupporting
confidence: 91%